Transport in developing countries and climate policy: suggestions for a Copenhagen agreement and beyond - Daniel Bongardt; Frederic Rudolph; Wolfgang Sterk (Wuppertal Institut für Klima, Umwelt, Energie, 2009)
Also in the global South, transport already significantly contributes to climate change and has high growth rates. Further rapid motorisation of countries in Asia and Latin America could counteract any climate efforts and aggravate problems of noxious emissions, noise and congestion. This Paper aims at connecting the need for transport actions in developing countries to the international negotiations on a post-2012 climate change agreement. It outlines the decisions to be taken in Copenhagen and the preparations to adequately implement these decisions from 2013. Arguing, that a sustainable transport approach needs to set up comprehensive policy packages, the paper assesses the substance of current climate negotiations against the fit to sustainable transport. It concludes that the transport sector's importance should be highlighted and a significant contribution to mitigation efforts required. Combining the two perspectives lead to several concrete suggestions: Existing elements of the carbon market should be improved (e.g. discounting), but an upscale of the carbon market would not be an appropriate solution. Due to a lack of additionality, offsetting industrialised countries' targets would finally undermine the overall success of the climate agreement. Instead, a mitigation fund should be established under the UNFCCC and financed by industrialised countries. This fund should explicitly enable developing countries to implement national sustainable development transport and mobility policies as well as local projects. While industrialized countries would set up target achievement plans, developing countries should outline low carbon development strategies, including a section on transport policy. – – Die rasante Motorisierung Asiens und Lateinamerikas könnte die Klimaschutzerfolge konterkarieren. Bis 2030, so Prognosen der IEA, werden im Verkehrssektor 2,5 Gigatonnen CO2 mehr emitiert als heute; 80 Prozent davon in den Ländern des Südens. Das Papier soll die Notwendigkeit verdeutlichen, dass in den Entwicklungsländern im Verkehrssektor heute schon Maßnahmen ergriffen werden müssen und die Klimaverhandlungen für die Post-Kyoto-Phase eine wichtige Gelegenheit sind. Die Ansätze in den gegenwärtigen Klimaverhandlungen werden den Anforderungen einer nachhaltigen Verkehrspolitik gegenübergestellt und dafür plädiert, den Stellenwert des Verkehrssektors zu den Klimaschutzanstrengungen zu erhöhen. Dafür werden mehrere konkrete Vorschläge gemacht: So sollten vorhandene Elemente des Emissionshandels verbessert werden, die eigentlich angemessene Lösung sei jedoch ein neues Instrument: Um die Entwicklungsländer in die Lage zu versetzen Maßnahmen in der Verkehrspolitik umzusetzen und Politiken und Projekte vor Ort zu fördern, sollte ein von den Industrieländern finanzierter Klimaschutzfonds unter dem UN-Klimaregime eingerichtet werden. In Strategien für eine kohlenstoffarme Entwicklung sind dabei die Politikinstrumente einer nachhaltigen Verkehrsentwicklung zu integrieren.
urn:nbn:de:101:1-2009052229
Keywords: 330